A COMPARATIVE STUDY BETWEEN TEACHING PROCEDURE TEXT BY USING DEMONSTRATION AND THINK PAIR SHARE (TPS) METHODS - Harahap, Olivia Feby Mon (Jurnal Kesehatan Ilmiah Aufa Royhan, 2017)
The aim of this study is to increase students there is the comperative of demonstration and TPS methosd in teaching procedure textat the grade seventh students of SMP N 4 Padangsidimpuan. The method of this research is experimental method. The population of research is 320 respondents and the sample of the research with the cluster sampling is 80 respondents. The data was collected by giving the test for both methods that contains 20 items for test. The result of analyzes data get the mean of variable X is 72,5 with the category “good” and the mean of variable Y is 66,5 with the category “enaough”. The calculationofttest is 3.02 and ttableis 2.00 , it can be seen from samples are 80 students where N1 = 40 students and N2 = 40 students. So, df (N1+N2)-2 = (40+40)-2 = 80-2 = 78. Thus, the score of ttable 2.00 of 5% significant degree. The result of the analyzed data shows the score of ttest> ttable= 3.02> 2.00. ). In other words, the score of ttest is higher than ttable. It can be stated that there is a significant comparison between demonstration and dThink pair sharemethods in teaching procedure text at the seventh grade students of SMP Negeri 4 Padang sidimpuan. So, the hypothesis is accepted.